The Role of Authentic Leadership In Human Resources Development: An Analytical Study In Diyala State Company - Radhi Abbas*, Ali; Matook Abood Al- Mahdi, Mohammed (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research works to achieve several objectives, the most important of which is determining the type of relationship between authentic leadership and human resource development and its dimensions. Theoretical Framework: In light of what was proposed by researchers(Walumbwa et al., 2008), (Ivancevich, 2002), this study helps public organizations on the one hand and the company being studied as well as identify the level of employees’ awareness of authentic leadership and The positives that leadership can contribute to developing human resources. Design/Methodology/Approach: conducted in Diyala State Company (2024) by distributing (180) valid questionnaires that were analyzed using advanced statistical methods using the authentic leadership model with its dimensions (self-awareness, ethical perspective, relationship transparency, balanced treatment) in human resources development (guidance, training, career path development, performance evaluation). Findings: The most essential results indicate no significant relationship between authentic leadership and human resource development. Research Implications: Authentic leadership plays a significant role in developing human resources within a company. This indicates that leadership is transparent, honest, and communicates effectively, which enhances performance and increases employee efficiency. Originality/Value: This study works to identify the importance of authentic leadership and areas of human resource development at various levels of the company being studied, whether at the individual or organizational level.